IMPROVING STUDENTS’ WRITING SKILLS OF RECOUNT TEXT BY APPLYING TRANSITION-ACTION-DETAILS (TAD) STRATEGY - arief muhsin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT This research aimed to explain how the use of the Transition-Action-Details (TAD, hereafter) Strategy improved students’ skills in writing Recount Text dealing with the content of writing. It also aimed to explain how the TAD Strategy improved students’ skills in writing Recount Text dealing with the organization of writing. Employing CAR as the reseaech design, the research findings indicate that TAD Strategy improves students’ writing skills of Recount Text. It was proven by the writing Recount Text of the students’ mean score in cycle 2 test result (78.95). This improved from the cycle 1 mean score (68.95). It improved significantly from diagnostic test (D – test) mean score (61.04). The writing Recount Text of the students’ achievement in cycle 2 indicated that it had met the score target (70.00), and considered to be successful criteria in improving the writing Recount Text through TAD Strategy. Based on the findings above, the author concluded that using TAD Strategy could improve the writing Recount Text of the students. ABSTRAK Penelitian ini bertujuan untuk menjelaskan bagaimana penggunaan Strategi Transisi-Aksi-Detail (TAD, selanjutnya) Strategi meningkatkan keterampilan siswa dalam menulis Recount Text yang berhubungan dengan isi tulisan. Ini juga bertujuan untuk menjelaskan bagaimana Strategi TAD meningkatkan keterampilan siswa dalam menulis Recount Text yang berhubungan dengan organisasi penulisan. Temuan penelitian menunjukkan bahwa TAD Strategy meningkatkan keterampilan menulis siswa dari Recount Text. Hal ini terbukti dengan penulisan Recount Text dari nilai rata-rata siswa dalam hasil tes siklus 2 (78,95). Ini meningkat dari skor rata-rata siklus 1 (68,95). Ini meningkat secara signifikan dari tes diagnostik (D-test) skor rata-rata (61,04). Tulisan Recount Text tentang pencapaian siswa dalam siklus 2 menunjukkan bahwa mereka telah memenuhi target skor (70,00), dan dianggap sebagai kriteria yang berhasil dalam meningkatkan penulisan Recount Text melalui TAD Strategy. Berdasarkan temuan di atas, penulis menyimpulkan bahwa menggunakan TAD Strategy dapat meningkatkan penulisan Recount Text dari para siswa. How to Cite: Muhsin, M. A. (2017). Improving Students’ Writing Skills of Recount Text by Applying Transition-Action-Details (TAD) Strategy. IJEE (Indonesian Journal of English Education), 4(2), 156-167. doi:10.15408/ijee.v4i2.2430